FORMATION OF CONSTRUCTIVE BEHAVIOR AS A FACTOR IN THE EFFECTIVENESS OF SCHOOLCHILDREN'S EDUCATION - Norkozieva Dilrabo Sheralievna (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses some issues of changing the aggressive behavior of schoolchildren in the process of organizing educational activities in a constructive direction, as well as some socio-psychological factors for its elimination, reflecting the ongoing psycho-prophylactic and psycho-corrective work. in education and family relations.